Descartes' philosophy and epistemology - Katea, Dr.Alaa Jassim (Thi Qar Arts Journal, 2024)
Research Topic: Descartes' Philosophy and Epistemological TheoryDescartes is considered the father of modern philosophy, a view first held by German philosophers such as Hegel and Schelling. Interest in Descartes is perpetual, with continuous and renewed writings about the philosopher who has become a hallmark of modern Western philosophy. Studies about him in various languages delve deeper, seek new insights, and revisit previous writings, reflecting his significant influence across generations.Descartes likened his philosophy to a tree: its roots are metaphysics, its trunk is natural science, and its branches are medicine, mechanics, and ethics. He rebelled against his era, criticizing the theoretical and contemplative philosophy taught in schools for its sterility and lack of practical utility in understanding phenomena. He advocated for a more practical philosophy beneficial to life, drawing its principles from modern physics intertwined with mathematics. Descartes believed that God is the true guarantor of all truths, bestowing the human mind with the first self-evident truths characterized by clarity and simplicity, which form the foundation of human sciences.Epistemology, in its general sense, refers to the study of the nature, essence, source, value, obstacles, conditions, and means of knowledge. Some consider epistemology a branch of theoretical psychology that cannot do without metaphysics, as its purpose is to investigate the principles assumed by thought. This means that epistemology examines the philosophical problems arising from the relationship between the perceiving subject and the perceived object, and between the knower and the known. Since the self must direct its thinking towards something, existence becomes the subject of knowledge. As a philosophical concept, existence refers to absolute reality, opposed to non-existence. This reality can be external or mental; external existence refers to the being of something in reality, while mental existence refers to the being of something in the mind, which is intellectual existence.